Abdominal Compartment Syndrome: Risk Factors, Diagnosis, and Current Therapy. (7th June 2012) - Luckianow, Gina M.; Ellis, Matthew; Governale, Deborah; Kaplan, Lewis J.
Abstract : Abdominal compartment syndrome's manifestations are difficult to definitively detect on physical examination alone. Therefore, objective criteria have been articulated that aid the bedside clinician in detecting intra-abdominal hypertension as well as the abdominal compartment syndrome to initiate prompt and potentially life-saving intervention. At-risk patient populations should be routinely monitored and tiered interventions should be undertaken as a team approach to management.